2019
DOI: 10.1016/j.devcel.2019.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Serial Synapse Formation through Filopodial Competition for Synaptic Seeding Factors

Abstract: Highlights d Stochastic filopodia dynamics are required for robust synapse formation in fly brains d Only 1-2 filopodia at a time contain synaptic seeding factors and are synaptogenic d 4D tracking and computational modeling support a serial synapse formation model

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 60 publications
(91 reference statements)
4
59
0
Order By: Relevance
“…Considering that the R7 growth cone begins to form presynaptic terminals in layer M6 65 hr after puparium formation (APF) (Chen et al, ), it would be interesting to determine whether extension begins before or after this stage. Recent study from Hiesinger group suggested that the synapse formation stabilizes the extended filopodia through live imaging experiment (Özel et al, ). If that is the case, it is possible that the major cause of the ectopic synapse formation in the klg mutant is due to the enhancement of the filopodia dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…Considering that the R7 growth cone begins to form presynaptic terminals in layer M6 65 hr after puparium formation (APF) (Chen et al, ), it would be interesting to determine whether extension begins before or after this stage. Recent study from Hiesinger group suggested that the synapse formation stabilizes the extended filopodia through live imaging experiment (Özel et al, ). If that is the case, it is possible that the major cause of the ectopic synapse formation in the klg mutant is due to the enhancement of the filopodia dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether the alterations in neurotransmission and vision were due to altered numbers of synapses, we generated sparse clones of photoreceptors R1-R6, and R7 expressing the active zone marker GFP-Brp short . This marker specifically localizes to presynaptic active zones without affecting synaptic development or function and is suitable for live imaging 14,33 . Loss of autophagy resulted in a 25%-80% increase in synapse numbers, while increased autophagy in rescued atg6 mutant photoreceptors reversed this effect and significantly reduced synapse numbers (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…the speed or stability of filopodial interactions, is almost completely unknown for dense brain regions in any organism. Our limited understanding of the dynamics of synaptogenic encounters reflects the difficulty to observe, live and in vivo , synapse formation at the level of filopodial dynamics in intact, normally developing brains 13,14 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations